2015
DOI: 10.1111/inr.12168
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of resilience in Chinese older people

Abstract: Greater insight into the psychological constructs of resilience in Chinese older people can lead to international comparisons and to the potential development of interventions for this population around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Resources that can contribute to growth and fostering of resilience may help nurses to promote a positive adaptation toward successful aging. 13 Enhanced resilience helps older people to manage the negative impact of changes in health 13 and may enable them to become more independent. 14 Health care providers need to have a clear understanding of resilience based on humans’ experiences in the specific context of their society.…”
Section: Introductionmentioning
confidence: 99%
“…Resources that can contribute to growth and fostering of resilience may help nurses to promote a positive adaptation toward successful aging. 13 Enhanced resilience helps older people to manage the negative impact of changes in health 13 and may enable them to become more independent. 14 Health care providers need to have a clear understanding of resilience based on humans’ experiences in the specific context of their society.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience The 25-item Resilience Scale (RS) [32] will be used to measure resilience (i.e., the outcomes of successful adaptation despite challenging or threatening circumstances of participants). This scale is reliable (test-retest reliability = .8; Cronbach's α = .95) for Chinese elderly populations [33]. The exploratory principal component analysis also found that RS was valid in a four-factor structure.…”
Section: Physical Attributesmentioning
confidence: 72%
“…No major difficulties were found in the translation procedure. The process of back translation was used in order to achieve semantic equivalence because the English version of the instrument was translated and not the original version (Yang et al 2015). Content validity was found to be highly satisfactory, as the CVI-I and the S-CVI/Ave exceeded the recommended values.…”
Section: Discussionmentioning
confidence: 99%